Consensus Defined Diastolic Dysfunction and Cardiac Postoperative Morbidity Score: A Prospective Observational Study - Bonnie Kyle (MDPI AG, 2021)
Diastolic dysfunction is associated with major adverse outcomes following cardiac surgery. We hypothesized that multisystem endpoints of morbidity would be higher in patients with diastolic dysfunction. A total of 142 patients undergoing cardiac surgical procedures with cardiopulmonary bypass were included in the study. Intraoperative assessments of diastolic function according to the 2016 American Society of Echocardiography and European Association of Cardiovascular Imaging guidelines using transesophageal echocardiography were performed. Cardiac Postoperative Morbidity Score (CPOMS) on days 3, 5, 8, and 15; length of stay in ICU and hospital; duration of intubation; incidence of new atrial fibrillation; 30-day major adverse cardiac and cerebrovascular events were recorded. Diastolic function was determinable in 96.7% of the dataset pre and poststernotomy assessment (n = 240). Diastolic dysfunction was present in 70.9% (n = 88) of measurements before sternotomy and 75% (n = 93) after sternal closure. Diastolic dysfunction at either stage was associated with greater CPOMS on D5 (p = 0.009) and D8 (p = 0.009), with CPOMS scores 1.24 (p = 0.01) higher than in patients with normal function. Diastolic dysfunction was also associated with longer durations of intubation (p = 0.001), ICU length of stay (p = 0.019), and new postoperative atrial fibrillation (p = 0.016, OR (95% CI) = 4.50 (1.22–25.17)). We were able to apply the updated ASE/EACVI guidelines and grade diastolic dysfunction in the majority of patients. Any grade of diastolic dysfunction was associated with greater all-cause morbidity, compared with patients with normal diastolic function.